Interview with Alec Leighton - Barkow, Jerome; Leighton, Alec (Anthropologica, 2022)
Anthropology and psychiatry have long provoked and stimulated one another, thanks to the efforts of individuals working in the overlap between them. Alexander Hamilton Leighton is one such figure, a researcher who has been not so much a bridge between disciplines as a winch, drawing the two fields closer to one another despite resistance. Leighton is currently Professor of Psychiatry and Professor of Community Health and Epidemiology at Dalhousie University in Halifax, Nova Scotia, Canada. He is also Professor Emeritus of Social Psychiatry at Harvard University's School of Public Health. He is a man in motion, rotating regularly between Halifax, Boston (his wife, Jane Murphy, is Associate Professor of Anthropology at Harvard University), and his home in southwestern Nova Scotia. Leighton was born on July 17, 1908, in Philadelphia, Pennsylvania. He received his B.A. from Princeton University in 1932, an M.A. from Cambridge in 1934, and his M.D. from Johns Hopkins in 1936. His research and teaching interests have ranged widely (a list of his publications follows this interview), but anthropologists will associate his name with the Stirling County study, a project conducted in Canada's Nova Scotia.